Two highly divergent lineages of exfoliative toxin B-encoding plasmids revealed in impetigo strains of Staphylococcus aureus - Botka, Tibor; Růžičková, Vladislava; Svobodová, Karla; Pantůček, Roman; Petráš, Petr; Čejková, Darina; Doškař, Jiří (International journal of medical microbiology, 2017)
Exfoliative toxin B (ETB) encoded by some large plasmids plays a crucial role in epidermolytic diseases caused by Staphylococcus aureus. We have found as yet unknown types of etb gene-positive plasmids isolated from a set of impetigo strains implicated in outbreaks of pemphigus neonatorum in Czech maternity hospitals. Plasmids from the strains of clonal complex CC121 were related to archetypal plasmid pETBTY4. Sharing a 33-kb core sequence including virulence genes for ETB, EDIN C, and lantibiotics, they were assigned to a stand-alone lineage, named pETBTY4-based plasmids. Differing from each other in the content of variable DNA regions, they formed four sequence types. In addition to them, a novel unique plasmid pETB608 isolated from a strain of ST130 was described. Carrying conjugative cluster genes, as well as new variants of etb and edinA genes, pETB608 could be regarded as a source of a new lineage of ETB plasmids. We have designed a helpful detection assay, which facilitates the precise identification of the all described types of ETB plasmids.
Keywords: Virulence; pemfigus; dermatotoxiny; Exfoliatins; Bacteriocins; impetigo; Whole Genome Sequencing; Exfoliative toxin B; DNA bakterií; bakteriální proteiny; Bacterial Proteins; DNA, Bacterial; lidé; exfoliatiny; Bullous impetigo; Staphylococcus aureus; virulence; Phylogeny; Pemphigus; ETB plasmids; plazmidy; Impetigo; Czech Republic; sekvenování celého genomu; bakteriociny; Česká republika; Plasmids; fylogeneze; Dermotoxins; Humans